2018
DOI: 10.12688/f1000research.14284.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of implementation of “mental health nursing students’ clinical competency model” on academic performance of nursing students

Abstract: Clinical nursing competence in mental health is one of the most Background: important topics in theoretical and practical nursing training with many factors affecting it. The purpose of this study is to determine the impact of the implementation of the "mental health nursing students' clinical competence model" on nursing students' academic performance.: This study is a semi experimental following one group of student Methods nurses. "mental health nursing students' clinical competence model" for undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Adequate teaching time is crucial for students because mental health competencies are based on the skills and information taught. 29 Mental health preparation should be relevant to practice and reflect changes in the healthcare system. For example, mental health care has shifted from acute care units and hospitals to more community-based care, and mental health nursing education should incorporate this change.…”
Section: Educational Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate teaching time is crucial for students because mental health competencies are based on the skills and information taught. 29 Mental health preparation should be relevant to practice and reflect changes in the healthcare system. For example, mental health care has shifted from acute care units and hospitals to more community-based care, and mental health nursing education should incorporate this change.…”
Section: Educational Challengesmentioning
confidence: 99%
“…This results in students memorizing information for temporary recall and limits development of problem-solving skills. 31 In contrast, a concept-based curriculum provides students with selective information to apply and Nursing strategies to improve mental health education 29,31…”
Section: Content Vs Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses' lack of interest (LOI) in working in psychiatric settings is a major factor contributing to the shortage of nursing staff in these settings. A study reported that most nurses choose to work in psychiatric settings only when there is no other employment opportunity (7). Factors affecting their interest in working in psychiatric settings are their negative attitudes towards work in these settings (8), stress, and emotional burnout (9).…”
Section: Introductionmentioning
confidence: 99%
“…Another issue of concern is the increasing number of bachelor's degree students in nursing, which has caused worries regarding the graduates' preparedness for carrying out their responsibilities. This has been regarded as a debatable issue where insufficient knowledge exists (Atashzadeh-Shoorideh et al, 2018;Ghodsbin & Shafakhah 2008).…”
Section: Introductionmentioning
confidence: 99%